Evaluation of Power Indicators of the Automobile Engine - Abed Dhahad, Hayder; Hameed Alawee, Wissam; Marchenko, Andrii; Klets, Dmytro; Akimov, Oleg (International Journal of Engineering and Technology, 2018)
A method for estimating the power characteristics of the car engine in various driving regimes is proposed. It is determined that the volume of the free power (engine power reserve) allows the driver to implement the turning parameters and the time of its completion, which are set by the steering parameters, position and the speed of the steering wheels rotation. The engine power reserve is necessary to provide the required maneuverability indicators. The engine power during maneuvering is spent on overcoming the resistance to movement and on providing the impact controlled by the maneuver. The first component of the engine power can be called connected, and the second one can be called the free one or a controlled component. The received analytical expressions allow carrying out at the design stage a rational choice of capacity of the engine by the condition of maintenance of demanded properties of maneuverability. The developed method for constructing the refined acceleration characteristics of the engine makes it possible to determine the dynamic capabilities of the car, taking into account its design features and operating conditions.Â